Validity and internal consistency of a Hausa version of the Ibadan knee/hip osteoarthritis outcome measure - Akinpelu Aderonke O (Health and Quality of Life Outcomes, 2008)
Abstract Background The Ibadan Knee/Hip Osteoarthritis Outcome Measure (IKHOAM) was developed for measuring end results of care in patients with knee or hip OA in Nigeria. The purpose of this study was to validate a Hausa translation of IKHOAM in order to promote its use among the Hausa populations of Nigeria and other West African countries. Methods Sixty-seven patients with knee OA, literate in Hausa and English, recruited consecutively from all government hospitals in Kano were assessed on both English and Hausa versions of IKHOAM. The order of assessment with the versions was randomized and separated by 24 hours. Participants also rated their pain intensity on the Visual Analogue Scale. Data was analyzed using the Spearman Rank Order correlation and Cronbach's alpha. Results The participants (17 males, 50 females) were aged 55.7 ± 13.4 years. Participants' scores on the Hausa version correlated significantly with the original version (r = 0.67, p = 0.000) and with pain intensity scores on the Visual Analogue Scale (r = -0.24, p = 0.005). The Cronbach's alpha for correlation on the different parts of the Hausa version ranged between 0.28 and 0.95. Conclusion The Hausa version of IKHOAM meets the criteria for validity and internal consistency and may be used in the Hausa speaking parts of Nigeria and other West African countries.